(untitled) (Bangladesh Journal of Medicine, 2022)
Melioidosis has lately expanded its endemic areas to encompass the Indian subcontinent, despite being well-known in Southeast Asia and Northern Australia.Though cases have been reported from Bangladesh, it might be a significantly underdiagnosed cause of infection & death in this agricultural country. We report a case of melioidosis with multiple abscesses & fulminant sepsis in a 55-year-old farmer diagnosed based on pus samples, which revealed gram-negative bacillus Burkholderiapseudomallei. Bangladesh J Medicine 2022; 33: 308-311